ANALISA POLA PEMBELIAN KONSUMEN MENGGUNAKAN DATA MINING DENGAN ALGORITMA APRIORI (STUDI KASUS: EDUKITS BATAM CENTRE) - Lowensky, Elnas; Elisa, Erlin (Computer Science and Industrial Engineering, 2023)
The initial research purposes is to do the analyzing of data transaction for one of the stationary stores in Batam city, namely edukits Batam Centre, because the store is a well-known business and of course many consumers are interested, of course, a lot of data has been collected so far. From transactions that have occurred so far, these data are only stored in the form of archive files without being processed or used for future business progress. To analyze this research, the a priori algorithm association rule method was used, by analysing support value and as well as the confidence value that were set so that the results of this study obtained the support value for the Printing Paper category 71%, Accessories 74%, 77%, Other Equipment 88%, Glue and Adhesive 72%. By using the Apriori algorithm, 2 rules are obtained, namely the antecedent value of stationery, the consequent accessories resulting in a support value of 65% and confidence of 84.4%. Then the second rule is the antecedent of accessories, the consequent of writing instruments with a support value of 65% and a confidence value of 88.4%.